Study of Clove Plant (Syzigium sp) Productivity in the Siritaun Wida Timur District of East Seram Timur Regency - Rumalean, Hasan; Kamsurya, Marwan Yani; Botanri, Samin; Pattilow, Ibnu Rusmin; Banjar, Nawawi; Hadijah, Miranda H (Jurnal Agrohut, 2024)
This research aims to determine the productivity of clove plants (Zyzigium Sp.) in the Siritaun Wida Timur District of East Seram Timur Regency. Three selected villages chosen as research samples are ADM Keta Kwaos Village, ADM Keta Rumadhan Village, and ADM Liantasik Village. The type of research is quantitative descriptive, and the method used in this research is a survey. The respondents from each village constitute 30% of the total clove farmers. The research results show that clove plant production from 2017-2019 is relatively stable, but in 2018 the production drastically decreased. This is due to cultivation factors and climate change factors that occurred in the three villages.